Mapping Cumulative Environmental Effects, Social Vulnerability, and Health in the San Joaquin Valley, California - Huang, Ganlin (American Public Health Association, 2012)
To understand the social distribution of environmental hazards, methods to assess cumulative effects and their health implications are needed. We developed a cumulative environmental hazard index integrating environmental data on pollution sites, air quality, and pesticide use; a social vulnerability index to measure residents’ resources to prevent or mitigate health effects; and a health index. We found that communities in California’s San Joaquin Valley with high social vulnerability face more environmental burdens and have worse health conditions.